AKIBAT HUKUM BAGI PEMILIK SATUAN RUMAH SUSUN TERHADAP DEVELOPER RUMAH SUSUN YANG DINYATAKAN PAILIT OLEH PENGADILAN NIAGA - Teddy Francis; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2020)
The apartment developers who still have responsibility to the buyers and owners of the apartment units must do maneuvers to maintain the continuity of the company even in an economic crisis. However, when a developer is unable to pay their debt and is declared bankrupt, there will be legal consequences for the buyers and owners on the ownership of the apartment, considering that developer still has responsibility. According to the author's analysis, when the developer goes bankrupt, the main certificate of the apartment becomes bankruptcy property and will be auctioned. The impact for buyers/owners who are still in the PPJB (sale and purchase binding agreement) stage is the cancellation of the PPJB followed by the creation of a new PPJB with the new developer or the owner can choose not to continue purchasing the apartment and become a creditor who can claim compensation, the impact on owners in the AJB (sale and purchase deed)/certified stage is that they still have rights ownership of apartment. In conclusion, the legal consequences for buyers/owners of flat at the PPJB stage depend on the actions chosen by the curator and the buyer/owner after the bankruptcy. Owners/buyers with AJB and certificates keep their ownership. The author's suggestion is Indonesian Law should clarify the definition of bankruptcy property, improving protection of apartment owners in the Apartment Law, Bankruptcy and Suspension of Payment Law, and Job Creation Law, harmonizing the understanding of the necessity of making PPJB in front of a notary in Indonesia Law.